Evidence for the glia-neuron protein transfer hypothesis from intracellular perfusion studies of squid giant axons (The Rockefeller University Press, 1977)
Incubation of intracellulary perfused squid giant axons in [3H]leucine demonstrated that newly synthesized proteins appeared in the perfusate after a 45-min lag period. The transfer of labeled proteins was shown to occur steadily over 8 h of incubation, in the presence of an intact axonal plasma membrane as evidenced by the ability of the perfused axon to conduct propagated action potentials over this time-period. Intracellularly perfused RNase did not affect this transfer, whereas extracellularly applied puromycin, which blocked de novo protein synthesis in the glial sheath, prevented the appearance of labeled proteins in the perfusate. The uptake of exogenous 14C-labeled bovine serum albumin (BSA) into the axon had entirely different kinetics than the endogenous glial labeled protein transfer process. The data provide support for the glia-neuron protein transfer hypothesis.